Pelatihan Cutting Tanaman Hypoestes pada Mahasiswa Pendidikan Biologi - Harisanti, Baiq Muli; Hajiriah, Titi Laily; Dharmawibawa, Iwan Doddy (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
The objectives of this service activity are: 1) to introduce and train the abilities of students of the Department of Biology Education, Faculty of Applied Science and Engineering, Mandalika University of Education in plant cutting techniques in an effort to propagate hypoestes plants; and 2) teach which practical science is faster, the growth of hypoestes roots immersed in well water or B1 mixed water. Service activities are carried out within 1 day (plus follow-up activities in the form of observations for 3-6 days at each home). The stages of this service activity are: 1) introduction; 2) cutting practice activities; and 3) follow-up activities (observations). One day activity is devoted to the practice of cutting techniques, then the cut plants are immersed in water to observe root growth (observation for 3-6 days). Based on the results of the activity evaluation, it can be concluded that the purpose of this service activity has been achieved in accordance with expectations. This achievement can be seen from the student's ability to cut hypoestes plants, and students are able to grow the roots of the cut plants after 6 days of immersion.